SOME ASPECTS OF NATIONAL ECONOMIC DOCTRINE - Zubiashvili, Tamaz; Atanelishvili, Tamar (Ecoforum Journal, 2017)
Doctrines which substantiated introduction of market economy elements and priority of development of real sector , e.g. industry, at certain stage of the development of national economy have held an important place in the history of economic thought. Classes were the very first to develop such doctrines. (Silagadze, A., 1996, 2000, 2001, 2006-2016; Kharitonashvili, 2008; Silagadze, A. and Atanelishvili, T., 2006-2007, 2010-2011, 2013-2014). The issue was quite challenging at the first stage of building capitalism in Georgia (19th century). Niko Nikoladze, a Georgian public figure (1843-1928), emphasized the high priority of the issue in those times. (Nikoladze, N., 1960-2003; 2006; Gamezardashvili, D., 1983; Janelidze, O., 1988; Silagadze, A., (Editor), Atanelishvili, T., Goshadze, G., (Edit.), Demetrashvli, T., Zurabishvili, V. (Edit.) - 2005; Silagadze, A. and Atanelishvili, 2004). His attitudes are still important in post-Soviet Georgia which heavily depends on import. The fact is that instead of using rich local resources, Georgia tends to import goods which the country has a real ability to produce itself. Poor development of real sector of economy has remained an Achilles’ heel for years. Tourism is a priority for the country, but during economic crises tourist flows stop and if there is no alternative, the country will face a deep crisis. (valchrelidze, A., Silagadze, A., Keshelashvili, G., Gegia, D., 2011) According to the conclusion made in this article, Nino Nikoladze’s doctrine which complies with "classic" attitudes, complies with both "classic" and national economic doctrines of Germany. It also complies with Ilia Chavchavadze’s economic doctrine with the difference that Ilia believed that agriculture was of highest priority while Niko Nikoladze believed industry to be the most important. In general, his economic doctrines implies priority development of national industry, deepening of west-east sea and railway ties, construction of ports, supporting of export, careful demilitarization, and improvement of market mechanisms of price formation, etc.